Effect of Lipid Materials on the Production of Lipase by Torulopsis ernobii - Yoshida, Fumihiko (1968)
The yeast Torulopsis ernobii produced approximately 50 units of extracellular lipase (glycerol ester hydrolase, E.C. 3.1.1.3) per ml when grown in 30-liter fermentors at 33 C for 40 hr in a base medium at pH 5.0. The addition of fats, oils, triglycerides, or higher fatty acids to this medium at concentrations of 0.2 to 0.6% markedly increased production; twofold increases in yield were obtained when 0.2% olive oil or a mixture of 0.14% oleic acid and 0.04% palmitic acid was added. The production of lipase paralleled growth, and the role of lipid materials in augmenting lipase production appears to be related to cell growth.